Pengalaman Kerja dan Etos Kerja serta Pengaruhnya terhadap Kinerja Anggota Kelompok Tani Setia Tani Hutan Pariksabungan - Marto Silalahi; Kevin Indajang; Pawer Derasa Panjaitan; Sudung Simatupang; Marthin Hutler Ambarita (Universitas Batanghari Jambi, 2023)
Good human resources today are the benchmark for the success of an organization, and this can be supported by the work experience and work ethic of the members of the organization. The purpose of this study is to determine the influence of work experience and work ethic on the performance of members of the Pariksabungan Forest Farmers Loyal Farmer Group working in Pinus Hills Simarjarunjung in Pariksabungan Village, Dolok Pardamena District, Simalungun Regency, which has 35 members. For the items of the research instrument, the results are obtained that can be declared valid and also reliable. The results of the regression were found to result that work experience and work ethic have a positive direction towards member performance. For hypothesis test results it was found that work experience has a positive and significant influence on member performance, similarly the influence of work ethic also has a positive and significant influence on member performance. When members of the organization have a more dominant work experience and are supported by a good work ethic, it will produce good performance which will directly support organizational performance.